Multidisciplinary tumor boards in oral cavity cancer: survival effect due to balancing guideline adherence and treatment delays - Burkhardt, Valentin; El-Shabrawi, Katharina; Riemann, Sarah; Voss, Pit; Becker, Christoph (Frontiers in Oral Health, 2024)
ObjectivesThe purpose of the study was to assess the impact of a pretherapeutic Multidisciplinary Tumor Board (MTB) presentation on the prognosis and treatment outcomes in patients with primary oral cavity carcinoma.Materials and methodsThis single-center study included 630 patients diagnosed with oral cavity carcinoma treated between 2010 and 2020. The study cohort was divided in a group with and without pretherapeutic MTB presentation. Data on patient demographics, tumor characteristics, treatment and the time to treatment initiation (TTI) were collected retrospectively.ResultsPrimary findings revealed no significant difference in 3-year survival rate (3-YSR) and 3-year disease-free survival rate (3-YDFSR) for the non-MTB and MTB group. The 3-YSR was 73.1% in the non-MTB group and 67.1% in the MTB group (p = 0.112). The 3-YDFSR was 73.8% in the non-MTB group and 76.5% in the MTB group (p = 0.447). Estimated mean 5-year survival (5-YS) and 5-year disease-free survival in (5-YDFS) did not differ significantly between both groups, across the UICC stages I-IV, as well as for the entire cohort. The TTI was significantly longer in the MTB group (33.5 days, CI: 31.3;35.7) compared to the non-MTB group (20.1 days, CI: 17.9;22.4, p < 0.001). The MTB group adhered more frequently to the national guidelines (68% vs. 79.6%, p < 0.01).ConclusionThe results demonstrate both positive and negative side effects of the MTB presentation in patients with oral cavity cancer. Further multicenter studies will be required to assess the impact of TTI and adherence to guidelines on the survival of oral cavity cancer patients.